2015
DOI: 10.4049/jimmunol.1403114
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Tolerance in Isotype Switch–Competent Anti-Insulin B Lymphocytes

Abstract: B lymphocytes that escape central tolerance and mature in the periphery are a liability for developing autoimmunity. IgG insulin autoAbs that predict type 1 diabetes and complicate insulin therapies indicate that mechanisms for tolerance to insulin are flawed. To examine peripheral tolerance in anti-insulin B cells, we generated C57BL/6 mice that harbor anti-insulin VDJH-125 site-directed to the native Ig H chain locus (VH125SD). Class switch-competent anti-insulin B cells fail to produce IgG Abs following T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 64 publications
2
29
1
Order By: Relevance
“…The Ca ++ /NFAT pathway is also active in B cells rendered tolerant to a low-affinity natural self-antigen (insulin) but, in this case, without uncoupling of NF-κB signaling (Acevedo-Suarez et al 2006). The resulting imbalance in different NFATs maintains tolerance in nonautoimmune B6 mice (Bonami et al 2014;Williams et al 2015). However, in genetically autoimmune mice, these B cells are recruited into GCs and produce autoantibody (Wan et al 2016).…”
Section: Signals Regulating Fate Choicementioning
confidence: 99%
“…The Ca ++ /NFAT pathway is also active in B cells rendered tolerant to a low-affinity natural self-antigen (insulin) but, in this case, without uncoupling of NF-κB signaling (Acevedo-Suarez et al 2006). The resulting imbalance in different NFATs maintains tolerance in nonautoimmune B6 mice (Bonami et al 2014;Williams et al 2015). However, in genetically autoimmune mice, these B cells are recruited into GCs and produce autoantibody (Wan et al 2016).…”
Section: Signals Regulating Fate Choicementioning
confidence: 99%
“…Further, in the absence of class switch recombination, it is impossible to assess the production of IgG autoantibodies, which are currently the most accurate predictors of T1D development in genetically susceptible individuals (18)(19)(20). To address how a fully functional, anti-insulin VH gene impacts disease, we targeted VDJH125 to the IgH chain locus in embryonic stem cells and used them to produce C57BL/6 (B6) and NOD mice harboring an anti-insulin VH (V H 125 SD ) (21,22).…”
mentioning
confidence: 99%
“…In non-autoimmune-prone B6 mice, these autoreactive B cells do not generate insulin autoantibodies spontaneously or in response to T-dependent immunization with heterologous insulin, and they have impaired proliferation to anti-CD40 and insulin in vitro. However, tolerance can be reversed following combined BCR/TLR stimulation, which results in Ag-specific germinal center responses and Ab production (21). Whether tolerance is similarly maintained in an autoimmune environment, however, is unknown.…”
mentioning
confidence: 99%
“…Studies in the autoreactive Ig models of B cell anergy have shown that anergic B cells can mount an antibody response under various conditions, such as stimulation with highly multimerized antigens and/or strong toll-like receptor stimulation [5557]. As such, a strategy designed to activate the peripheral pool of anergic B cells in bnAb Ig knockin mice would be expected to provide insight for vaccination approaches.…”
Section: Immunological Tolerance As a Barrier To Protective Hiv-1 Hummentioning
confidence: 99%